Discovery, identification, and functional characterization of long noncoding RNAs in Arachis hypogaea L. - Haiying Tian; Feng Guo; Zhimeng Zhang; Hong Ding; Jingjing Meng; Xinguo Li; Zhenying Peng; Shubo Wan (BMC Plant Biology, 2020)
Abstract Background Long noncoding RNAs (lncRNAs), which are typically > 200 nt in length, are involved in numerous biological processes. Studies on lncRNAs in the cultivated peanut (Arachis hypogaea L.) largely remain unknown. Results A genome-wide scan of the peanut (Arachis hypogaea L.) transcriptome identified 1442 lncRNAs, which were encoded by loci distributed over every chromosome. Long intergenic noncoding RNAs accounted for 85.58% of these lncRNAs. Additionally, 189 lncRNAs were differentially abundant in the root, leaf, or seed. Generally, lncRNAs showed lower expression levels, tighter tissue-specific expression, and less splicing than mRNAs. Approximately 44.17% of the lncRNAs with an exon/intron structure were alternatively spliced; this rate was slightly lower than the splicing rate of mRNA. Transcription at the start site event was the alternative splicing (AS) event with the highest frequency (28.05%) in peanut lncRNAs, whereas the occurrence rate (30.19%) of intron retention event was the highest in mRNAs. AS changed the target gene profiles of lncRNAs and increased the diversity and flexibility of lncRNAs, which may be important for lncRNAs to execute their functions. Additionally, a substantial number of the peanut AS isoforms generated from protein-encoding genes appeared to be noncoding because they were truncated transcripts; such isoforms can be legitimately regarded as a class of lncRNAs. The predicted target genes of the lncRNAs were involved in a wide range of biological processes. Furthermore, expression pattern of several selected lncRNAs and their target genes were examined under salt stress, results showed that all of them could respond to salt stress in different manners. Conclusions This study provided a resource of candidate lncRNAs and expression patterns across tissues, and whether these lncRNAs are functional will be further investigated in our subsequent experiments.